Is there a peer status gradient in mortality? Findings from a Swedish cohort born in 1953 and followed to age 67. (28th February 2023) - Almquist, Ylva B; Östberg, Viveca; Modin, Bitte
Abstract: Background: Similar to having a less advantaged socioeconomic position, children in lower peer status positions typically experience a situation characterized by less power, influence and command over resources, followed by worse health outcomes. The aim of this study was to examine whether peer status position is further associated with increased risks for premature all-cause mortality. Methods: Data were drawn from a 1953 cohort born in Stockholm, Sweden. Peer status positions were established through survey data on peer nominations within the school class at age 13, whereas national registers were used to identify all-cause mortality across ages 14–67. Differences in hazard rates and median survival time, according to peer status position, were estimated with Cox regression and Laplace regression, respectively. Results: Although differences in hazard rates were not large, they were consistent and clear, also after taking childhood socioeconomic status into account. Regarding median survival time, the number of years lost increased gradually as peer status decreased, with a difference of almost 6 years when comparing individuals in the lowest and highest positions. Conclusions: Children's positions in the peer status hierarchy play a role for their chances of health and survival, pointing to the relevance of addressing opportunities for positive peer interaction and mitigating any adverse consequences that may stem from negative experiences within the peer context.